Causal Theories of Mental Content: Where Is the ‘Causal Element’ and How Does It Make Intentionality Relational? - Gilaitis, Mindaugas (Problemos, 2016)
This paper has two interrelated aims. The primary aim is to specify the character of philosophical theories of mental content that are usually classified as ‘Causal Theories of Intentionality’, ‘Causal Theories of Representation’, or ‘Causal Theories of Mental Content’ (CTs). More specifically, the aim is to characterize the role and place of causation in philosophical reflections on the nature of mental content, as suggested by theories of this kind. Elucidation of the role of the concept of causation in CTs requires examining the philosophical background against which versions of CTs are proposed; therefore the second aim of this paper is to clarify the link between CTs and the two philosophical theories that accompany it: the doctrine of philosophical naturalism (PN) and the representational theory of mind (RTM). Clarification of the relationship between the three theories is not only necessary for an adequate specification of the causal component that plays a central role in CTs, and so for a better understanding of CTs themselves; it also shows how the role that causation plays in CTs implies a genuinely relational conception of intentionality.
Keywords: Causal Theories of Mental Content; Intentionality; Naturalism; Representational Theory of Mind